(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2014)
If the light path is disrupted, huge volume of traffic loss occurs. Failure of connection may be due to fibre cut or node failure in the network.Survivability, the ability of a network to withstand and recover from failures, is one of the most important requirements of networks. Its importance is magnified in fibre optic networks with throughputs on the order of gigabits and terabits per second. In this paper survivable strategies are Dynamic Path Protection, Shared Path Protection and Hybrid Connection Approach.These strategies are compared on the basis of blocking probability,Resources Utilization Ratio and number of wavelength link used for the establishment of connection request.The network topologiesNATIONAL and NSFNET have been used for simulation on MATLAB environment. The result demonstrates that among all the strategies HCA establish maximum number of connections; avoid congestion and uses minimum network capacity.